„Pozycja prawie idealna”. Związek Polskich Artystów Plastyków wobec przemian politycznych, kryzysu gospodarczego i napięć środowiskowych w latach 1980–1981 - Banasiak, Jakub (Artium Quaestiones, 2021)
This paper examines the participation of the Polish Artists' Union in the complex transformation of communist Poland in 1980–1981 . It is one of the most mythologized phenomena in Polish art history. The main approach to this period assumes that before the of “Solidarity” movement uprising, the Polish Artists' Union was totally dependent on the communist authorities. Then, after August 1980, the Union was to become idealistic, anti-communist organization. The following paper recognizes this kind of historiographical narrative as an example of the 'totalitarian model'. It is a model based on a simple, binary vision of the communist system as a field of permanent struggle between “innocent” society and “oppressive”, omnipotent authorities. The analysis presented here uses the perspective of social history (Sheila Fitzpatrick et al.). From this perspective, communism is viewed as a complex tangle of active, causative social actors (groups and individuals), who could be politically engaged, but may not be. One of those actors was the Polish Artists' Union. Based on various kinds of sources, I show how the Union tried to take the optimal political position after August 1980. To examine this issue I use two types of political mentality, which dominated in those days in the Party, in “Solidarity”, and also in the Union. One is termed “fundamental”, and treats politics in terms of morality, dignity, and so on. The other is called “pragmatic”, and is focused on institutional games, while also allowing compromises or concessions. To track the dynamics of how the Union functioned from August 1980 until martial law was declared (in December 1981), I introduce a division into three phases of the Solidarity revolution: September-December 1980, January-July 1981, and September-December 1981. An analysis of the Union's documents, art magazines, and Party's documents (both official and internal), shows that after the first phase, the Polish Artists' Union was ready to join the new configuration of power, based on Solidarity and the Polish United Workers' Party agreement. According to David Ost's theory, I define this project as a “neo-corporatist” model of the state socialism in the art system.